Blood coagulation system state in breast cancer patients that recovered from coronaviral infection after undergoing antitumor medical treatment - L. Yu. Vladimirova; E. M. Frantsiyants; N. A. Abramova; K. A. Novoselova; V. S. Myagkova; O. V. Katelnitskaya; A. E. Storozhakova; I. L. Popova; S. N. Kabanov; N. M. Tikhanovskaya; E. A. Kalabanova; L. A. Ryadinskaya; et al. (Исследования и практика в медицине, 2022)
Purpose of the study. An analysis of parameters of the blood coagulation system in breast cancer patients after coronavirus disease.Materials and methods. 50 breast cancer patients were divided into groups: the main group included 30 patients after coronavirus disease, the control group 1–20 patients without confirmed COVID‑19, and control group 2–20 non-cancer women after corona‑ virus disease. All cancer patients received appropriate chemotherapy. The following parameters were studied: activated partial thromboplastin time (APTT), prothrombin time (PT), international normalized ratio (INR), prothrombin index (PTI), fibrinogen, soluble fibrin monomer complexes (SFMCs), thrombin time (TT), antithrombin III, D-dimer and plasminogen, fibrin degradation products. Blood tests were performed 4–6 weeks after the infection and two negative PCR test results for COVID‑19.Results. Patients of the main group demonstrated differences in INR values after treatment in the subgroups with asymptomatic disease (Me = 1.24) and with mild symptoms (Me = 0.97) U = 10; Z = 2.766; р = 0.0057, in subgroups with asymptomatic disease (Me = 1.24) and with moderate to severe symptoms (Me = 0.98) U = 26.5; Z = 2.199; р = 0.027, and in TT values in subgroups with asymptomatic disease (Me = 14.5) and with moderate to severe symptoms (Me = 16.5) U = 18.5; Z = –2.725; р = 0.0064. The comparison of the parameters in patients after COVID‑19 before (Me = 0.83) and after treatment (Me = 0.4) showed differences in the D-dimer values in patients with moderate to severe disease U = 6.5; Z = –2.2861; р = 0.022 towards their decrease after the therapy. Differences were found in APTT values between the main group (Me = 30.65) and control group 1 (Me = 27.85) U = 119; Z = 3.574; р = 0.00035, in antithrombin values between the main group (Me = 94) and control group 1 (Me = 106) U = 112; Z = 3.713; р = 0.00021, and in SFMCs values between the main group (Me = 17) and control group 1 (Me = 8) U = 180.5; Z = 2.356; р = 0.018.Conclusions. Determination of plasminogen levels can become an independent factor in detecting thrombotic risk in cancer patients who recovered from COVID‑19. Previous infection with COVID‑19 should be considered an additional risk factor for venous thromboembolic complications for cancer patients.